2006
DOI: 10.1158/1078-0432.ccr-06-1273
|View full text |Cite
|
Sign up to set email alerts
|

Diallyl Trisulfide Suppresses Growth of PC-3 Human Prostate Cancer Xenograft In vivo in Association with Bax and Bak Induction

Abstract: Purpose: The present study was undertaken to determine the effect of garlic constituent diallyl trisulfide (DATS) on growth of PC-3 human prostate cancer xenograft in vivo. Experimental Design: DATS was given orally (6 AmoL, thrice weekly) to male athymic mice s.c. implanted with PC-3 cells. Tumor sections from control and DATS-treated mice were examined for apoptotic bodies by terminal deoxynucleotidyl transferase^mediated dUTP nick end labeling assay. Protein levels of apoptosis and cell cycle regulating pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
89
0
2

Year Published

2007
2007
2009
2009

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 111 publications
(100 citation statements)
references
References 43 publications
9
89
0
2
Order By: Relevance
“…Second, the PrEC normal prostate epithelial cell line is significantly more resistant to growth inhibition and apoptosis induction by DATS even at concentrations that are highly cytotoxic to the prostate cancer cells. Third, we have shown recently that oral administration of DATS (6 Amol, thrice per week) significantly retards growth of PC-3 xenografts in vivo in athymic mice in association with apoptotic cell death (42).…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Second, the PrEC normal prostate epithelial cell line is significantly more resistant to growth inhibition and apoptosis induction by DATS even at concentrations that are highly cytotoxic to the prostate cancer cells. Third, we have shown recently that oral administration of DATS (6 Amol, thrice per week) significantly retards growth of PC-3 xenografts in vivo in athymic mice in association with apoptotic cell death (42).…”
Section: Discussionmentioning
confidence: 92%
“…The present study indicates that Bax and Bak proteins play an important role in the regulation of DATS-induced apoptosis because (a) the SV40-immortalized MEFs derived from DKO mice are significantly more resistant toward DATS-induced cell death compared with the WT MEFs; (b) the DATS-mediated cytosolic release of cytochrome c and cleavage of procaspase-3 is relatively more pronounced in the MEFs derived from WT mice than in the MEFs derived from DKO mice; and (c) Bax and Bak knockdown in LNCaP cells confers statistically significant protection against DATS-induced apoptosis. We have shown recently that the DATS-mediated inhibition of PC-3 xenograft growth in athymic mice in vivo correlates not only with increased apoptosis but also induction of Bax and Bak proteins in the tumor tissues (42). It is important to point out, however, that Bax and Bak cannot fully explain the cell death caused by DATS because combined knockdown of these proteins confers only partial protection against DATS-induced apoptosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies, Bak1 and Bax were reported to regulate apoptotic signaling in CaP synergistically. Knockdown of Bak1 and Bax completely prevented the apoptosis induced by a variety of biological molecules and chemical compounds (33)(34)(35)(36). Bak1 expression has also been reported to be associated with the progression of CaP.…”
Section: Discussionmentioning
confidence: 93%
“…Diallyl trisulfide-mediated inhibition of PC-3 xenograft growth was accompanied by induction of proapoptotic Bcl-2 proteins Bak and Bax. 35 Garlic has been explored in prostate cancer prevention studies, and a relative decreased risk of prostate cancer was noted in consumers of garlic in an Asian population, supporting its possible use as an interesting agent in future studies. 36 In summary, initial anti-Bcl-2 approaches have been attempted in prostate cancer.…”
Section: Bcl-2 Familymentioning
confidence: 95%